Lesson learned from implementation of green building concepts towards sustainable development: A case study of a state-owned enterprises (BUMN) head office in Cilacap - Vitriana Vitriana; Hermawan Ferry; Kurniati Rina (E3S Web of Conferences)
The building sector has a role in contributing to climate change, which occurs by 37%, so the transition to sustainable development is carried out. Green building, which is one of the manifestations of sustainable development, is a planning concept that is still voluntary, and in Indonesia, only 4% has been recorded. This research was conducted to study the implementation of the green building concept specifically so that the main building of BUMN in Cilacap, Central Java, was determined. From observations and interviews, the benefits and challenges of implementing the green building concept were obtained, which serves as an illustration for other businesses in implementing the idea. The benefits include the potential for decarbonization with the use of renewable energy, comfort for occupants, and operational cost savings. In contrast, future challenges include maintaining the commitment of each building user to continue to conserve and the implementation of feasibility provisions at the beginning. Recommendation to improve: it is necessary to routinely monitor and evaluate or audit the commitments made, implement appreciation measures for employees and sanctions for violators, involve certified experts in building management in the operational stage, and integrate supporting data in the system as a form of good internal communication.